2016
DOI: 10.1590/1809-2950/15214123032016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de linfedema após tratamento de câncer de mama em pacientes com sobrepeso

Abstract: RESUMO O câncer de mama é a neoplasia de maior ocorrência no mundo, e o linfedema é uma das complicações mais frequentes do tratamento. O aumento do índice de massa corporal é um dos fatores de risco para linfedema após o tratamento do câncer de mama. O objetivo deste estudo foi verificar a incidência de linfedema em mulheres mastectomizadas com sobrepeso e obesidade. Os resultados mostraram que o risco de linfedema em mulheres com sobrepeso e obesidade foi quatro vezes maior (Odds Ratio, OR=3,887). Quanto mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
2
Order By: Relevance
“…12,13 A BMI between overweight and obesity (≥ 25 kg/m) was observed in 78.4% of women with lymphedema, which is line with the literature that points out to overweight or obesity as a risk factor for lymphedema. 1,6,14 An observational study carried out with 100 women investigated the prevalence of lymphedema in overweight or obese women who underwent mastectomy and it found that overweight women are twice as likely to have lymphedema, and for those who have level 1 obesity, the risk of developing this comorbidity is around six times higher. 6 Another prospective study with 787 women with breast cancer assessed the impact of pre-operative BMI and the change in weight after treatment on the incidence of lymphedema and it concluded Lymphedema after breast cancer Gozzo TO, Aguado G, Tomadon A, Panobianco MS, Prado MAS that a BMI over 30 in the pre-operative period is an independent risk factor for lymphedema and a weight fluctuation of 4.5 kg per month (gain or loss) during the post-operative period results in a higher risk for lymphedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 A BMI between overweight and obesity (≥ 25 kg/m) was observed in 78.4% of women with lymphedema, which is line with the literature that points out to overweight or obesity as a risk factor for lymphedema. 1,6,14 An observational study carried out with 100 women investigated the prevalence of lymphedema in overweight or obese women who underwent mastectomy and it found that overweight women are twice as likely to have lymphedema, and for those who have level 1 obesity, the risk of developing this comorbidity is around six times higher. 6 Another prospective study with 787 women with breast cancer assessed the impact of pre-operative BMI and the change in weight after treatment on the incidence of lymphedema and it concluded Lymphedema after breast cancer Gozzo TO, Aguado G, Tomadon A, Panobianco MS, Prado MAS that a BMI over 30 in the pre-operative period is an independent risk factor for lymphedema and a weight fluctuation of 4.5 kg per month (gain or loss) during the post-operative period results in a higher risk for lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…This build up is the result of a lymph system failure in the homolateral limb, generally triggered by surgical procedures and/or radiotherapy in the axillary region. [4][5][6] The diagnosis of lymphedema can be made by means of subjective criteria with the symptoms reported by the patient, such as a feeling of heaviness, swelling, and reduced limb mobility, or by means of objective criteria such as circumference, volumetry, ultrasonography, and spectroscopic bioimpedance. 7,8 Most women with breast cancer-related lymphedema have altered mobility in the affected limb, thus making daily activities and routine more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…A incidência do linfedema varia em diferentes estudos, sendo observada em aproximadamente 20% dos casos [7]. A retirada dos linfonodos axilares é o principal fator de risco para ocorrência do linfedema [8].…”
Section: Introductionunclassified
“…2 Studies reveal that obese women are more prone, being the chance up to four times greater when compared to those with normal weight . 3 Lymphedema in the arm may have repercussions on physical and psychological well-being, caused both by the reduction of the limb functionality and by the body aesthetic. 4 Instruments have already been validated to evaluate the body image of breast cancer women, such as Body Image Index (BII), Sexual Adjustment and Body Image Scale (SABIS), Body Image after Breast Cancer Questionnaire (BIBCQ) and Body Image and Relationship Scale (BIRS).…”
Section: Introductionmentioning
confidence: 99%